Differentiated Instruction Strategies for Students with Learning Disabilities - Rahimi, Hasan (Psychological Research in Individuals with Exceptional Needs, 2023)
The objective of this study was to explore and identify effective differentiated instruction (DI) strategies for students with learning disabilities in mainstream educational settings. This qualitative research involved semi-structured interviews with 21 participants, including general education teachers, special education teachers, and educational administrators from an urban school district. Participants were selected through purposive sampling, ensuring a diverse representation of educators with extensive experience in teaching students with learning disabilities. Data collection continued until theoretical saturation was achieved. Thematic analysis was conducted to identify patterns and themes related to DI strategies, perceived effectiveness, implementation challenges, and support mechanisms. The study identified several key DI strategies, including differentiated content, process, product, and environment, along with the integration of technology. These strategies were reported to enhance student engagement, academic achievement, and social-emotional development. However, significant challenges such as time constraints, limited resources, and the need for professional development were highlighted. Support mechanisms, including professional development opportunities, collaborative practices, administrative backing, community resources, parental engagement, and technological support, were identified as crucial for successful DI implementation. Differentiated instruction is an effective approach to addressing the diverse needs of students with learning disabilities, promoting inclusivity and improving educational outcomes. Despite its benefits, the successful implementation of DI requires addressing substantial challenges through targeted support mechanisms. Future research should focus on expanding the sample size, exploring long-term impacts, and investigating the role of technology in DI. Practical recommendations include enhancing professional development, fostering collaboration, securing administrative support, engaging community resources, and increasing parental involvement.